Dreaming and Sleeping in the Children’s Poetry of Laura E. Richards - Jennifer Lewin (European Journal of American Studies)
This article claims that the children’s poetry of Laura E. Richards deserves more critical attention for its modeling in verse of a specific kind of intimate caregiver-child relationship. It especially examines the roles of sleep and dreams in In My Nursery as defining that connection not only through human interactions but especially through the child’s engagement with the natural world. By having plants, flowers, trees, and animals conspire to facilitate the regulation of sleep habits, Richards also brings these poems into dialogue with a longstanding tradition. Poems about sleep and dreams since ancient times and specifically in the early modern period have reconciled opposites such as vulnerability and control; Richards’s sleepers find themselves performing similar work with the help of external human and environmental support.